Evaluation Of Glutathione Disulphide On Oil Palm Seedlings (Elaeis guineensis) At Nursery Stage - Wong, Yen Siang (2017)
In the oil palm industry, increasing yield productivity without further land expansion is an important priority for big companies and smallholders. Glutathione disulphide (GSSG) has the potential to promote seedling growth and increase palm fruit productivity. This study was conducted to evaluate the effect of GSSG on the growth of oil palm seedlings grown under nursery and greenhouse conditions. The seedlings were tested with two forms of GSSG that were liquid and granules. After 120 days of growth in the greenhouse, seedlings were harvested and determined for dry weight, chlorophyll content and nutrients content. The antioxidant activities of the seedlings were compared with three different assays namely DPPH, FRAP and metal chelating assay. All parameters measured were then statistically analyzed.